ANALYSIS OF LEVEL OF INFECTIOUS MORBIDITY AMONG SERVICEMEN OF MILITARY POWERS OF UKRAINE ON INDEXES OF 2001-20011 уу. - Rozhkov, G.S. (World of Medicine and Biology, 2012)
Conducted analysis of level of infectious morbidity of servicemen after 2001-2011, showed that during 2001-2011, the level of infectious morbidity among all contingents of servicemen averaged 46,08‰, that in 1,6 times a more middle level of infectious morbidity is among citizenry. Differences between the indexes of morbidity among servicemen of urgent service and officers, servicemen of military service by contract, can be related first of all to the lacks of preventive vaccines of infectious diseases among a pre-conscription contingent, especially child's "guided" infections.
Keywords: Military Powers of Ukraine; infectious morbidity; categories of servicemen